Reduction in body temperature using hand cooling versus passive rest after exercise in the heat - Adams, W. M.; Hosokawa, Y.; Adams, E. L.; Belval, L. N.; Huggins, R. A.; Casa, D. J. (Journal of Science and Medicine in Sport, 2016)
Objectives: To examine the effects of hydration and hand cooling on lowering body temperature after exercise in the heat. Design: Randomized cross-over design. Methods: Nine recreationally active male participants (mean ± SD; age, 24 ± 4; height, 177.3 ± 9.9 cm; body mass, 76.7 ± 11.6 kg; body fat, 14.7 ± 5.8%) completed a bout of treadmill exercise in a hot environment. After completion of exercise, participants were assigned to the following trials for post-exercise cooling: (1) hydrated with passive rest (HY), (2) hydrated with hand cooling on both hands (HY + 2HC), (3) dehydrated with passive rest (DY), and (4) dehydrated with hand cooling on both hands (DY + 2HC). Within subject differences were assessed using a three-way (Hydration x Condition x Time) repeated measures ANOVA with Tukey's post hoc analysis if significant interactions were found. Results: Irrespective of hydration status, hand cooling on both hands resulted in significantly greater reductions in TREC than passive cooling at minute 20 (0.27°C [0.05, 0.49], ES = 2.08, p = 0.017) (Fig. 1). The reduction in TREC at minute 18 trended towards statistical significance (0.21°C [.003, .42], ES = 1.59, p = 0.053). Hydration status alone and when differentiated among modes of cooling showed no differences on changes of TREC or heart rate across all conditions during post exercise recovery (p > 0.05). Conclusions: Hand cooling on both hands reduced TREC more than passive cooling, however, the cooling rates observed render hand cooling a poor option for cooling. Greater reductions in TREC after exercise or between bouts of exercise may enhance recovery and subsequent performance.